PENGARUH PENAYANGAN IKLAN DARING SELAMA PANDEMI COVID-19 TERHADAP KOGNISI KONSUMEN AKAN KEBUTUHAN DAN DAMPAKNYA TERHADAP PERILAKU PEMBELIAN KONSUMEN - Cynthia Cynthia; Sherly Sherly; Fidelius Marlfel; Marlyn Marlyn; Keni Keni (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Online ads which are basically faster, more effective, and more accurate tend to be more engaging than traditional ads. The influence of online ads does not happen instantly, other factors contribute to the changes in consumer behavior to become more impulsive. Consumer need for cognition is the factor that mediates the relationship. Consumers who have need for cognition tend to be more easily influenced by online ads, especially when it's done repeatedly. Therefore, this study was conducted to examine the relationship between repeated online ads and consumer need for cognition for the changes in consumer behavior that was strengthened or weakened by the COVID-19 pandemic. Hypothesis testing was carried out by using Partial Least Square - Structural Equation Modeling (PLS-SEM) analysis with SmartPLS software. The research results showed that repeated online ads and consumers' need for cognition had a positive influence on consumer buying behavior, but the COVID-19 pandemic had a negative effect.